THE RESISTANCE OF BRAHMAN CROSS CATTLE IN PADANG CITY, WEST SUMATRA - Dianti, Devi; Fridarti; Syafrizal; Mulyani, Sri; Hendri, Jhon; Palwa Suryani, Novia; Erwin (Department of Agriculture, 2024)
The research aims to determine Brahman cross (BX) cattle's heat resistance at the UPT Aia Pacah, Padang, West Sumatra. The research variables were the “Temperature Humidity Index (THI)”, calculated based on changes in environmental temperature and air humidity, and “Heat Resistance” measured according to the Benezra and Rhoad coefficients. The calculation of heat resistance is based on physiological characteristics (body temperature, heart rate, and respiratory rate). Data was collected twice a day, in the morning and afternoon, on 40 BX cattles. The results of the morning and the afternoon research showed that the average THI was respectively 75.5 + 2.03 and 82.68 + 1.06, the average body temperature was 37.79 + 0.27 and 38.28 + 0.29 degrees Celsius, the respiratory rate was 19.04 + 1.87 and 25.68 + 1.33 breaths per minute, the heart rate was 52.80 + 6.09 and 59 + 5.96 beats per minute, heat resistance Based on the Benezra and Rhoad coefficients, they were 2.35 + 0.28 and 96.40 + 1.52. The conclusion is that BX cattles kept at the UPT Aia Pacah, Padang is in moderate stress conditions during the day, while the heat resistance of 2.35 is slightly above the normal value of 2 and the Road coefficient is 96.04.